“That’s when he comes rushing into her life.”: Swedish Literary Depictions of Human-Animal Sexual Contact at the Turn of the Twenty-First Century - Lönngren, Ann-Sofie (Humanimalia, 2020)
This essay discusses three literary narratives written by Swedish authors Elsie Johansson (1984), Gabriella Håkansson (2003) and Lars Jakobson (2004), which all depict human-animal sexual contact. The analysis shows that two of these representations are written in the intersection of a bestiality paradigm and a pet paradigm, thus depicting sexual contact between human and animal as ultimately lethal, although instigated by love. The third narrative sketches another world in which human-animal sexual and romantic relationships are part of everyday life; ultimately, however, this comes across as an unsatisfying solution for both parties. The outcome of the investigation is the proposal that, during the course of the twentieth century, a rural, communicative, male sodomy paradigm seems to have given way to one of urban, silent, female sexuality.